From film adaptation to post-celluloid adaptation : rethinking the transition of popular narratives and characters across old and new media - Constandinides, Costas (Continuum, 2010)
The main corpus of film adaptation thus far has focused on films based on canonical literature. From Film Adaptation to Post-Celluloid Adaptation takes the next logical step by discussing the emerging modes of film adaptation from older media to new, mainly focusing on the computer-generated reconstructions of popular narratives an d c haracters along with other forms of convergence such as the Internet. While 'New Media' is a broa d c oncept, the book will concentrate on the ways digital technology is being used in the encoding of films and discuss the ways this shift can be debated from a th.